2019
DOI: 10.1021/acsearthspacechem.8b00162
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Durability and Dissolution Kinetics of Iodoapatite in Aqueous Solutions

Abstract: Understanding the long-term release of radionuclides from nuclear waste to the environment is critical for public acceptance and sustainability of nuclear energy. Iodoapatite, a synthetic material similar to mineral vanadinite proposed for radioactive iodine-129 immobilization, is employed in this study as a model system for iodine waste forms and ceramic waste forms in general to understand its long-term chemical durability. Semidynamic leaching experiments were performed in cap-sealed Teflon vessels to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 74 publications
0
46
0
Order By: Relevance
“…Details of the synthesis and characterization of these samples were reported previously in separate publications. 25,29,37 The leaching method was adopted from ASTM C1308 standard test, as described in the previous study 29,37 . Four parallel experiments were conducted simultaneously for 14 days in four different leaching solutions: 0.1 mol/L NaCl, 0.1 mol/L Na2CO3, 0.1 mol/L Na3PO4, and 0.1 mol/L Na2SO4.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of the synthesis and characterization of these samples were reported previously in separate publications. 25,29,37 The leaching method was adopted from ASTM C1308 standard test, as described in the previous study 29,37 . Four parallel experiments were conducted simultaneously for 14 days in four different leaching solutions: 0.1 mol/L NaCl, 0.1 mol/L Na2CO3, 0.1 mol/L Na3PO4, and 0.1 mol/L Na2SO4.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, the trend of iodine released in Na2CO3 solution of pH 10.3 resembles that of leaching iodoapatite under pH 4. 37 Despite the rate difference, both surfaces leached by pH 4 and pH 10.3 formed secondary phases (chervetite and hydroxylvanadinite, respectively). Our previous study showed that the equivalent long-term rate of iodine release under pH 6 is 8.1 mmol/m 2 /d, over two magnitudes higher than that of the deionized water 0.036 mmol/m 2 /d.…”
Section: Effect Of Ph On Iodine Release and Secondary Phase Formationmentioning
confidence: 96%
See 3 more Smart Citations